Factors Contributing to Increase in Knee Osteoarthritis Among Young People of Multan Periphery - Shahid Javed, Zaka Ul Rehman, Muhammad Yosuf, Muhammad Naqash Khan, Umair Ahmad, Umair Iqbal, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the risk factors of knee osteoarthritis in young patients. Methods: A total of 100 patients with diagnosis of knee arthritis were included as cases and a similar number of 100 patients who presented to the orthopedic clinic for reasons other than knee arthritis were taken as controls. A study questionnaire was designed to gather information regarding the patient’s age, gender, body mass index, physical activity, smoking history and knee injury history. Results: Mean age was 39.1±6.8 years in study group and 40.2±5.7 years in control group. There were 67 (67%) male patients in cases group and 59 (59%) male patients in control group, p-value 0.24. There were 35% obese patients in cases and 13% in control group (p-value 0.0002). There were 56% smokers in cases and 41% in control group with p-value 0.03. Out of 100, 11% patients in cases and 4.0% in control group had history of knee joint injury (p-value 0.06). 47% patients in cases group and 33% patients in control group were belonged to hardworking occupations, p-value 0.04. Conclusion: Obesity, history of knee joint injury, smoking and hardworking occupation are risk factors of knee osteoarthritis in young patients. Keywords: Knee osteoarthritis, young patients, obesity, risk factors.